Impacts of balanced nutrient management systems technologies in the northern Guinea savanna of Nigeria - Akinola, Adebayo A.; Alene, Arega D.; Adeyemo, R.; Sanogo, D.; Olanrewaju, A.S. (2009)
As part of a major effort to address soil fertility decline in West Africa, a project on balanced nutrient management systems (BNMS) has been implemented in the northern Guinea savanna (NGS) of Nigeria. The project tested and promoted two major technology packages: a combinedapplication of inorganic fertilizer and manure (BNMS-manure) and a soybean/maize rotation practice (BNMS-rotation). This study used two-stage least squares regression models to examine the socio-economic impacts of the BNMS technologies on household incomes and food security of the adopting farmers. Results showed that average crop yields for maize, sorghum and soybean increased by more than 200% in the villages covered by the project. Among the adopters, the gross margin per ha from maize production was highest for the adopters of BNMS–rotation and lowest for adopters using inorganic fertilizer only. The two-stage least squares regression estimates indicated that increases in farm income due to adoption of BNMS technologies led to an increase of both calorie and protein intake of adopters. An additional one ha of land under BNMS–manure stimulates an increase in food expenditure by about 52%, while a similar change in land area under BNMS–rotation increases food expenditure by 128%.